Testing the biogeographical regionalization of the Mexican Transition Zone based on the distribution of Curculionidae (Insecta: Coleoptera) - García-Navarrete, Patricia G.; Morrone, Juan J. (Zootaxa, 2018)
A test of the biogeographical regionalization of the Mexican Transition Zone (MTZ) is presented, resulting from a Parsimony Analysis of Endemicity (PAE) based on the distributional patterns of 575 species of the family Curculionidae. The analysis was carried out in three stages. First, a PAE was carried out to define a general regionalization scheme for the MTZ, identifying areas and microareas of endemism for the entire area. Then PAEs were undertaken for each province. Third, a PAE was carried out to determine the relationship between the provinces of the MTZ. The analysis of the entire MTZ resulted in four areas and 57 microareas of endemism, while in the independent analysis of each province, five areas and 67 microareas of endemism were obtained. Both analyses coincide basically in the location of the areas and microareas of endemism, which are subordinated to biogeographic units defined by different authors. In the consensus cladogram of the third stage of the analysis, the Transmexican Volcanic Belt (TVB) is the sister area to the Sierra Madre Occidental (SMOC); then, they are the sister area to the Sierra Madre Oriental (SMOR); and finally the previous provinces are united in a trichotomy with the Sierra Madre del Sur (SMS) and the Chiapas Highlands (CHIS). It is assumed that the differences found when comparing our results with different cladistic biogeographic studies of the MTZ reflect the complexity of the study area. Since the data used to perform the analyses are not uniform, and both geographical units and taxa are different, the comparison between different analyses is difficult.